Legal Analysis of Artificial Intelligence in Corporate Board Rooms - et. al., Dinesh Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Artificial Intelligence has the potential to revolutionize the corporate boardrooms. AI has recently entered the corporate boardrooms. As per the literature available AI can be divided into three forms- assisted, augmented and autonomous artificial intelligence. There is a difference of opinion some scholars is of the view that AI can only be used as a tool or aid by boards while other believe in delegating the directors’ duties to AI for efficient results The author in this article will examine the technological development in field of AI and board of directors with special reference to India.